2021
DOI: 10.3389/fimmu.2021.658631
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune-Related LncRNA Pairs for Predicting Prognosis and Immunotherapeutic Response in Head and Neck Squamous Cell Carcinoma

Abstract: Long noncoding RNAs (lncRNAs) have multiple functions with regard to the cancer immunity response and the tumor microenvironment. The prognosis of head and neck squamous cell carcinoma (HNSCC) is still poor currently, and it may be effective to predict the clinical outcome and immunotherapeutic response of HNSCC by immunogenic analysis. Therefore, by using univariate COX analysis and Lasso Cox regression, we identified a signature consisting of 21 immune-related lncRNA pairs (IRLPs) that predicted clinical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Head and neck squamous cell carcinoma (HNSC) accounts for more than 90% of head and neck cancer, which is the sixth most common malignancy in the world; thereby, around 800,000 novel diagnoses are reported annually, according to the World Health Organization (WHO) (WHO [ 1 ], [ 2 , 3 ]). Depending on localization, HNSC can show very poor prognosis, which is furthermore influenced by differentiation, perineural invasion, depth, and diameter, as well as metastasis formation ([ 4 6 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Head and neck squamous cell carcinoma (HNSC) accounts for more than 90% of head and neck cancer, which is the sixth most common malignancy in the world; thereby, around 800,000 novel diagnoses are reported annually, according to the World Health Organization (WHO) (WHO [ 1 ], [ 2 , 3 ]). Depending on localization, HNSC can show very poor prognosis, which is furthermore influenced by differentiation, perineural invasion, depth, and diameter, as well as metastasis formation ([ 4 6 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, different immunological issues related to prognosis of HNSC have been raised during the past years; for example, infiltrating T-lymphocytes and regulatory T cells have been highlighted as important issues for HNSC prognosis and development ([ 7 , 8 ]). Accordingly, the role of immunomodulation and potentially related biomarkers in therapy and diagnosis of HNSC has become an emerging field ([ 2 , 3 , 9 , 10 ]). Alongside with this aspect, the genetic and epigenetic mechanisms and related pathways have been highlighted ([ 11 13 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a 14-IRGP signature was developed as a novel prognostic marker for predicting survival of patients with head and neck squamous cell carcinoma [ 37 ]. As for IRLP signature, one study identified a 21-IRLP signature to predict the clinical outcomes and immunotherapeutic responses in case of head and neck squamous cell carcinoma [ 38 ]. However, this is the only relevant study about IRLP signature in tumor so far.…”
Section: Discussionmentioning
confidence: 99%
“…One study has highlighted the value of the 21 immune-related lncRNA pairs signature as a predictor of prognosis and immunotherapeutic response in HNSCC. 87 Also, by pairing immune-related lncRNAs, Yin et al. have established a signature, concerning specific expression levels, to predict the immune landscape of HNSCC, thus guiding the clinical therapy of HNSCC patients.…”
Section: Mechanism Of Lncrnas In Hnsccmentioning
confidence: 99%